Potret Industri Informal di Pedesaan Priangan Timur - Charina, Anne; Kusumo, Rani Andriani Budi; Mukti, Gema Wibawa (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The informal industry is currently experiencing considerable development in several developing countries, including Indonesia. The most significant development can be seen from the increasing number of informal industries growing, especially in rural areas. This research tries to photograph the development of informal industries that are growing in rural East Priangan. Using a qualitative approach, data was collected by interviewing 20 informal industry owners in rural East Priangan. Thematic analysis with N-vivo version 12 software was used to analyze the data obtained. This research reveals that the portrait of informal industries that are widely operated in East Priangan includes the local food-based snack industry, micro scale, this industry only relies on family labor with non-routine production process activities. However, this business is considered flexible, easy and cheap by the perpetrators and the demand tends to be stable even though it is very small